Rare Reported Left Hepatic Subcapsular Biloma and Management - Sarah Brown; Pablo Giuseppucci; Christopher Esper (Case Reports in Surgery)
Subcapsular bilomas are a rare complication of laparoscopic cholecystectomy and an even more rare occurrence to occur spontaneously. We present a case of left sided subcapsular biloma following a laparoscopic cholecystectomy. The location of the biloma was unrelated to our area of dissection. The operation was without difficult dissection or pressurization of the biliary tree. In addition, we present percutaneous drainage alone, without ERCP as adequate management in subcapsular bilomas.